The incidence of, and risk factors for, liver injury in adults living with human immunodeficiency virus initiating antiretroviral therapy in a South African private sector managed care cohort - Sinha, Suniti (Department of Public Health and Family Medicine, 2026)
Introduction Hospital surveys found that drug-induced liver injury is a leading adverse reaction resulting in hospitalization and death in people living with HIV (PLHIV) in South Africa. Objectives To determine incidence of, and risk factors for, liver injury and liver injury-related hospitalizations in PLHIV on antiretroviral treatment (ART). Methods We described the incidence of, and associations with, ALT³120 IU/L, ALT³200 IU/L, and hospitalizations with raised ALT in PLHIV aged >18 years in the Aid for AIDS private sector cohort (comprising medical scheme beneficiaries) commencing ART between 2011–2018. Results We included 92,757 PLHIV; median age was 38.4 years; 42.5% were male, and 88.6% were on efavirenz-based ART. Incidence per 100 person years (95% confidence interval (CI)) of ALT³120IU/L, ALT³200IU/L, hospitalization with ALT³120IU/L, and hospitalization with ALT³200IU/L was 0.93 (0.89-0.97), 0.38 (0.36-0.41), 0.06 (0.05-0.07), and 0.04 (0.03-0.05), respectively. Adjusted hazard ratios (aHRs) (95% CI) for ALT³120IU/L and hospitalization with ALT≥120IU/L respectively were 15.3 (12.1-19.3) and 6.27 (3.11-12.6) for antituberculosis drug exposure; 1.63 (1.31-2.02) and 1.50 (0.70-3.20) for efavirenz; and 2.74 (2.04-3.69) and 3.48 (1.24-9.73) for nevirapine, compared to protease inhibitors. AHRs (95%CI) for ALT³200IU/L and hospitalization with ALT≥200IU/L respectively were 12.6 (9.31-17.1) and 5.68 (2.58-12.5) for antituberculosis drug exposure; 1.74 (1.28-2.37) and 1.97 (0.69-5.58) for efavirenz; and 3.01 (1.97-4.61) and 3.56 (0.93-13.65) for nevirapine. Suniti Sinha SNHSUN002 All HRs adjusted for age, sex, CD4 count and viral load at ART initiation, and alcohol-induced pathology. Conclusions Exposure to antituberculosis drugs was strongly associated with liver injury. Safer antituberculosis treatment regimens are needed for PLHIV.